The Relationship Between the Extrinsic Environment of the Residence and the Incidence of ISPA in the Working Area of the Medan Johor Health Center - Nindy Rahmalila Putri; Meutia Nanda (Universitas Ibn Khaldun Bogor, 2023)
ISPA is carried by infectious agents in the form of viruses and bacteria. This study aims to determine the relationship between the distance of residence to the highway and industry as well as the destruction of waste against ARI disease in the community in the Medan Johor Health Center work area. ISPA is caused by an unclean environment, extrinsic factors in the form of a home environment close to the highway and industry, and the process of waste destruction has a major impact on human health, especially the respiratory tract. This study used a quantitative type with a sectional research design. The research sample consisted of 87 respondents with the Lemeshow formula. Sampling technique with Purposive Sampling technique. Data processing and analysis were carried out with Chi-Square and the results were known to be <0.05. The results showed that Highways and Household Waste Destruction affect ARI disease, except for industries that are not related to ARI disease in the Medan Johor Health Center work area. It is expected to provide education to the community in the form of counseling from the Medan Johor Health Center and Health Cadres in coordination with the local sub-district, to always maintain personal hygiene and the surrounding environment.